Research Progress of Electrical Stimulation in Ischemic Heart Disease - Zhao, Ying; Wang, Pengyu; Chen, Zhe; Li, Manman; Zhang, Dengfeng; Yang, Liming; Li, Hong (Frontiers in Cardiovascular Medicine, 2021)
Ischemic heart disease (IHD) is a considerable health burden worldwide with high mortality and morbidity. Treatments for IHD are mainly focused on decreasing oxygen demand or increasing myocardial oxygen supply, including pharmacological, interventional and surgical treatment, but there are also some limitations. Therefore, it is important to find a simple, effective and economical treatment. As a noninvasive and safe physiotherapy, electrical stimulation (ES) has a promising application in the treatment of IHD. Current studies suggest that ES can affect the occurrence and development of IHD by promoting angiogenesis, regulating autophagy and apoptosis, inhibiting inflammatory response and oxidative stress. In this review, we focus predominantly on the mechanism of ES and the current progress of ES therapy in IHD, furthermore, gives a brief on the forms of ES in clinical application.